Celebration of Nature and Culture through Gaura Parba: An Interdisciplinary Study of Environmental Stewardship and Cultural Sustainability - Awasthi, Prabeen Kumar (NPRC Journal of Multidisciplinary Research, 2024)
Gaura Parba, also known as Gaura Purnima or Gaura Tritiya, is an ancient Hindu festival celebrated predominantly in Uttar Pradesh, India, and in the Far Western Region of Nepal, represents  a unique amalgamation of nature, culture, and spirituality. This festival, dedicated to the worship of Goddess Gauri (an incarnation of Goddess Parvati), holds immense cultural and spiritual significance for the communities that observe it. However, beyond its religious connotations, Gaura Parba embodies a profound reverence for nature and serves as a conduit for the valorization of both natural and cultural heritage. This research explores Gaura Parba's significance in valorizing natural and cultural heritage within these communities. Employing an interdisciplinary approach encompassing various theoretical insights from cultural studies, anthropology, and environmental science, this study elucidates how Gaura Parba fosters a deep connection with nature and preserves cultural traditions. By examining the festival's rituals, beliefs, and environmental practices, the research explores the complex interplay between nature, culture, and spirituality within the context of Gaura Parba. The findings underscore Gaura Parba's contributions to ecological conservation, social cohesion, and the transmission of traditional knowledge, while also addressing contemporary challenges and opportunities for revitalizing the festival in the face of modernization and environmental change. This study provides valuable insights for scholars, policymakers, and practitioners aiming to enhance cultural resilience and sustainable development.